Species delimitation and speciation process in the Seriphium plumosum L. complex (Gnaphalieae: Asteraceae) in South Africa - Shaik, Zaynab (Department of Biological Sciences, 2020)
The remarkable richness of the Cape Floristic Region (CFR) and the high in situ diversification inferred for the region prompt interest in two key areas: first, to what extent has the true species richness of the Cape been discovered and described, and second, what are the key drivers of speciation? Steady efforts in taxonomy dating back to the early 17th century have led some to estimate that over 99% of species in the Cape flora have already been described. However, taxonomic research in the Cape has, as elsewhere, relied on morphology for delimiting species, implying that undiscovered species diversity among cryptic taxa may be substantial. Early ideas regarding the drivers of diversification in the Cape flora emphasised climatically-induced vicariant speciation. Since that time, both vicariance and ecological speciation have been invoked as drivers of diversification. However, the relative contributions of either of these modes to the richness of the flora remains unclear. The present work focuses on Seriphium plumosum, a species complex in the daisy tribe Gnaphalieae with a recent evolutionary origin and a core distribution in the Cape Floristic Region. The species’ problematic taxonomic history, its substantial morphological and ecological variability, as well as its large geographic distribution in southern Africa suggest that the current concept of the species houses multiple independent evolutionary species. Species limits within the complex are reevaluated using the Bayes Factor Delimitation method of Leaché et al. (2014) within an integrative taxonomic approach, incorporating evidence from next-generation DNA sequence data, previous taxonomic treatments, morphology, ecology and geographic distribution. The drivers of lineage divergence are then investigated at the population level within selected species in the group, with a focus on neutral and adaptive processes, and the spatial contexts within which each of these processes is thought to operate. The evidence presented here provides support for ten or eleven independent evolutionary species housed within the current concept of S. plumosum. The species currently considered sibling to the complex, Seriphium cinereum, is strongly supported as embedded within the complex, which I thus term the S. plumosum clade. In order to better facilitate identification of the species, several of the evolutionary species uncovered are consolidated. As such, a total of nine species are described in the taxonomic treatment of the clade, each of which is morphologically and ecologically cohesive, and five of which qualify as biological species sensu Mayr (1969). These include S. plumosum1 and S. cinereum under new circumscriptions, four new species; Seriphium alto-argillaceum, S. burrowsii, S. crypticum and S. dunensis, and three species housed within the current concept of S. plumosum and formerly treated within Stoebe; Seriphium burchellii Levyns, S. vulgaris Levyns, and S. virgatum Thunb. At the population level within selected species in the S. plumosum clade, neutral processes and weak divergent selection within a spatially discontinuous context are supported as the key driver of differentiation. These findings suggest that phylogenetic niche conservatism and/or the limited dispersal abilities characteristic of many Cape clades have been important in diversification by neutral and adaptive processes in the region. If extrapolatable to other Cape lineages, this work implies that undiscovered species diversity in the Cape may considerably exceed recent estimates, and that the role of non-adaptive processes in generating species diversity may be considerably underestimated.